2019
DOI: 10.2337/cd18-0027
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Transition Readiness of Adolescents With Type 1 Diabetes Using the Transition Readiness Assessment Questionnaire

Abstract: IN BRIEF This study aimed to assess readiness to transition from pediatric to adult health care in adolescents with type 1 diabetes using the Transition Readiness Assessment Questionnaire (TRAQ). TRAQ is a non–disease-specific self-report measure that assesses self-management and advocacy skills of youth with special health care needs. This study provides guidance on assessing transition readiness scores of adolescents with diabetes and identifying when health care providers should intervene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…This study assessed the validity of the TRAQ 5.0 in a clinically referred sample of 237 16‐ to 18‐year‐old youth accessing CAMHS, with almost half of the sample presenting with clinically elevated scores on the YSR Anxious‐Depressed syndrome scale. This sample's mean total TRAQ 5.0 scale score (3.51) aligns with mean scores among youth with diverse (primarily physical) health conditions, which have ranged from 3.04 to 4.11 in previous studies (Beal et al, 2016 ; Chan et al, 2019 ; Eaton et al, 2017 ; Roth et al, 2019 ). These are, on average, lower than the mean score (3.93) reported by Beal and colleagues ( 2016 ) for youth with no medical conditions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study assessed the validity of the TRAQ 5.0 in a clinically referred sample of 237 16‐ to 18‐year‐old youth accessing CAMHS, with almost half of the sample presenting with clinically elevated scores on the YSR Anxious‐Depressed syndrome scale. This sample's mean total TRAQ 5.0 scale score (3.51) aligns with mean scores among youth with diverse (primarily physical) health conditions, which have ranged from 3.04 to 4.11 in previous studies (Beal et al, 2016 ; Chan et al, 2019 ; Eaton et al, 2017 ; Roth et al, 2019 ). These are, on average, lower than the mean score (3.93) reported by Beal and colleagues ( 2016 ) for youth with no medical conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Chronological age was also associated with higher TRAQ 5.0 scores, as expected, and the difference comprised an almost medium-sized effect (Cohen's D = .47). Previous studies of physical health have also found a difference in TRAQ score based on age (Chan et al, 2019;Little et al, 2017). Older youth may therefore not only be more developmentally prepared for transitions, but also have had more opportunity to prepare for and discuss transitions with their care providers than their younger peers.…”
Section: Discussionmentioning
confidence: 89%
“…The TRAQ survey was validated for adolescents with cystic fibrosis in the United States [ 28 ]. The questionnaire was used internationally, e.g., USA, England, Canada, and Italy, [ 28 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and adapted for other chronic conditions, but an adaptation of IBD is still missing [ 11 , 43 , 44 , 45 , 46 ]. Adapted versions are available in Spanish for patients diagnosed with various chronic diseases, in Thai, and Brazilian-Portuguese for rheumatologic disorders, for the American pediatric population with epilepsy, and in Turkish for adolescents with diabetes [ 11 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 ages 14-26 years with chronic conditions (type 1 diabetes, spina bifida, sickle cell disease, and congenital heart disease). 3,[7][8][9] Transition readiness was further measured using Skin Knowledge and Psychosocial tools. 10,11 All scores were measured on a 5-point Likert scale…”
Section: Collected Datamentioning
confidence: 99%